2014
DOI: 10.1007/s10551-014-2457-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Leadership Behavior and Employee Justice Perceptions: The Mediating Role of Trust in Organization

Abstract: Using data collected at two phases, this study examines why and how ethical leadership behavior influences employees' evaluations of organization-focused justice, i.e., procedural justice and distributive justice. By proposing ethical leaders as moral agents of the organization, we build up the linkage between ethical leadership behavior and the above two types of organization-focused justice. We further suggest trust in organization as a key mediating mechanism in the linkage. Our findings indicate that ethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
142
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(163 citation statements)
references
References 88 publications
11
142
0
10
Order By: Relevance
“…Ripley et al (2006), Komendat and Didona (2016) found that an employee's perception of the work environment influences behaviour and predict their performance. The perception among employees is an outcome of procedures being executed, hence the loyalty and motivation to work is the reflection of fairness (Xu, Loi and Ngo, 2016). Procedural justice as a dimension of organizational justice has been studied both negatively and positively (Vermunt and Steensma, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ripley et al (2006), Komendat and Didona (2016) found that an employee's perception of the work environment influences behaviour and predict their performance. The perception among employees is an outcome of procedures being executed, hence the loyalty and motivation to work is the reflection of fairness (Xu, Loi and Ngo, 2016). Procedural justice as a dimension of organizational justice has been studied both negatively and positively (Vermunt and Steensma, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on the positive consequences of ethical leadership are also numerous (for e.g. Xu et al, 2014;Babalola et al, 2014;Mayer et al, 2012;Elci et al, 2012;Den Hartog and Belschak, 2012;Neubert et al, 2009;Toor and Ofori, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ethical leaders demonstrate accountability, fairness, honesty and concerned for others and set standards for their followers (Brown & Treviño, 2006;Brown et al, 2005;Kalshoven et al, 2011;Xu et al, 2016). In this study, we focused on accountability and fairness as the aspects of ethical leadership and the links of these constructs with organizational learning.…”
Section: Discussionmentioning
confidence: 99%
“…Resick et al (2011) suggest that honesty, integrity, trustworthiness, sincerity, authenticity, self-discipline and courage and good intentions are important aspects of ethical leadership. In this study, following Brown & Treviño (2006) and Xu et al (2016), we focus on two aspects of ethical leadership -fairness and accountability -given the importance of these aspects for employee motivation, performance and productivity. Our choice of accountability is inspired by the argument that accountability is a key aspect that can overcome destructive practices and can contribute to economic and social development (Aguilera & Adera, 2008).…”
Section: Fairnessmentioning
confidence: 99%
See 1 more Smart Citation